أثر استخدام مدخل العلوم والهندسة والتكنولوجيا والرياضيات (STEM) في النمو المعرفي والاجتماعي لدى أطفال الرياض في مدينة حماة – دراسة شبه تجريبية (Journal of Hama University, 2022)
This study aimed at measuring effect of using approach of STEM on cognitive and social growth for kindergarten in Hama City. For these purposes, the researchers used scales of cognitive and social growth. Then, ten activities were designed according STEM. The sample consisted of experimental group (n=15) and control group (20). The research instruments were applied pre and post the experimental treatment on the two groups, depending on   quasi–Experimental approach. (SPSS) software was used for conducting the comparisons. The results of the study showed :There are statistically significant differences between the mean scores of  both experimental and control groups in the post-application of  scales of cognitive and social growth. These differences were in favor of  the experimental group kids who learned throughout the STEM activities.There are statistically significant differences between the mean scores of  experimental group kids in the pre and post-application of scales of cognitive and social growth. These differences were in favor of  the post-application.After learning experimental group kids by using of  STEM activities, cognitive growth increased (51.83%) and social growth increased (48.76%).Many suggestions were introduced in light of the results; generalizing using STEM in all educational stages.
Keywords: Keywords: STEM entrance, cognitive development, social development, kindergarten children.